CYPERMETHRIN AND SODIUM FLUORIDE SYNERGISTIC EFFECT ON OXIDATIVE ENZYMES IN MUSCLE AND KIDNEY OF ALBINO MICE - P. RAVI SEKHAR; Y. SAVITHRI; Y. PRAKASH RAO; S. KISHORE; K. JAYANTHA RAO (International Journal of Pharma and Bio Sciences, 2010)
Present study was aimed to investigate the synergistic effect of cypermethrin and sodium fluoride on oxidative enzymes. Albino mice were treated orally with cypermethrin and sodium fluoride individually and combination, for individual administration 1/10th LD50 of cypermethrin and sodium fluoride selected (i.e. 8.5 mg/kg body weight and 5.6 mg/kg body weight) and for combined administration 1/20th LD50 was selected (i.e 4.25mg/kg body weight and 2.8 mg/kg body weight) for 15 days and 30 days with 48 hours intervals. It reveals significant variation in glucose-6-phosphate dehydrogenase (G6PDH), lactate dehydrogense (LDH), succinate dehydrogenase (SDH) and glutamate dehydrogenase (GDH) activities. Glucose-6-phosphate dehydrogenase, lactae dehydrogenase and glutamate dehydrogenase activities were enhanced where as succinate dehydrogenase activity was decreased in muscle and kidney tissues of experimental animals. The Changes were more pronounced in combination treated tissues than individual treated tissues and it may be due to synergistic effect of cypermethrin and sodium fluoride.